Page 1 of 1

Deriving De Broglie's Equation

Posted: Sun Oct 13, 2019 8:35 pm
by Sean Sugai 4E
Using the equations c=λv, E=mc^2, and E=hv, how can you derive De Broglie's equation?

Re: Deriving De Broglie's Equation

Posted: Sun Oct 13, 2019 8:43 pm
by Rida Ismail 2E
how i did it is i used the equations E=pc, E=hv, and c=hv:

you first convert c=hv to v=c/λ
Then substitute v=c/λ into the v in E=hv giving you E=h(c/λ)
then set E=pc equal to E=h(c/λ), giving you pc=h(c/λ)
the c cancel
giving you p=h/λ
solve for λ
λ=h/p

Re: Deriving De Broglie's Equation

Posted: Sun Oct 13, 2019 8:56 pm
by Julie Park 1G
Given that E=mc2 and E=hv
Substitute E to get mc2=hv
Rearrange to get mc = (hv)/c = p
Note: If E=pc, and E=hv, then p=E/c can be rearranged to p=hv/c

Given that c=λv and p=(hv)/c, p=h/λ
Which can be rearranged to λ=h/p (De Broglie)